Digital Clinic System / Norsafina Bahari - Norsafina, Bahari (2004)
Web accessibility will be an essential component of the services that future clinics should provide for clients. The clinic's site will generate patient loyalty by providing convenient access (24 hours a day, 7 days a week) to the clinic's service , location and hours and provide them with immediate access to a wealth of contemporary, health related information. Following from that, Digital Clinic System has been developed to generate awareness and patient referrals and raise the clinic' image by demonstrating the leading edge, technological proficiency. Digital Clinic System allows patients to register and make an appointment with the doctor through Internet. On the administrator and doctor side, an application will be developed in a local environment, which provides more secure than online to maintin the system. To achieve the above requirements, the system is run is web-based Three-Tier client/server architecture. The backend include the database server and web server. Database server operates the "data access logic". The Microsoft Access store and process all data of the clinic and patient . The web server manages the operation of the LAN. It handles and distributes the request of client. IIS 5.0 will be used to connect front end the web server, so that ASP can be run to provide and environment for the script of the web server. The front end includes computer of doctors and staffs. Users access the system by using web browser.